2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25427
|View full text |Cite
|
Sign up to set email alerts
|

Growing Experimental Centric Learning: The Role of Setting and Instructional Use in Building Student Outcomes

Abstract: Dr. Yacob Astatke completed both his Doctor of Engineering and B.S.E.E. degrees from Morgan State University (MSU) and his M.S.E.E. from Johns Hopkins University. He has been a full time faculty member in the Electrical and Computer Engineering (ECE) department at MSU since August 1994 and currently serves as the Associate Dean for Undergraduate Studies in the School of Engineering. Dr. Astatke is the winner of the 2013 American Society for Engineering Education (ASEE) "National Outstanding Teaching Award," an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In-depth analysis identified that satisfaction with use and perceptions of positive outcomes increased as instructor familiarity with the ADBs and experimental pedagogy increased. As noted in previous reports 17,18 , first time student users and novice instructors indicated a need for more introductory materials, videos, and visual aids that would facilitate use.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…In-depth analysis identified that satisfaction with use and perceptions of positive outcomes increased as instructor familiarity with the ADBs and experimental pedagogy increased. As noted in previous reports 17,18 , first time student users and novice instructors indicated a need for more introductory materials, videos, and visual aids that would facilitate use.…”
mentioning
confidence: 74%
“…Further reviews indicated overlapping or simultaneous use of the ADBs varied by institution. Preliminary correlations of use indicated that higher use was positively related to higher outcomes 17 . Students reported a median independent use of 3-5 times a term; overall, 37% reported at least 6+ times of independent uses per semester.…”
Section: Finding: 2 Instructional Use: Application Of the Adbsmentioning
confidence: 97%
See 2 more Smart Citations
“…The mobile boards have also been utilized in other disciplines such as mechanical engineering using two experiments developed and tested in a class. [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%